Innovative Factors that Influence the Performance of Human Talent in Organizations - Morelos-Gómez, José; Cardona-Arbeláez, Diego; lora-Guzman, Harold (Journal of Ecohumanism, 2024)
The purpose of this research is to analyze the innovative factors that have an effective impact on the performance of human talent in organizations. A systematic literature review was carried out using the scientific database Scopus, for the time horizon of years 2015 to 2024, and the following keywords were established: innovation, human resources, human talent and innovation factors, the data was coded, which allowed filtering and selecting the most relevant articles, going from 454 documents to a final set of 37 articles included for the analysis. The analysis of innovation-related factors identified four key conceptual categories: a) knowledge acquisition and transfer; b) quality management and strategic financial control; c) technological assets and absorptive capacity, intellectual talent and psychological talent; and d) entrepreneurial orientation, social innovation and internal marketing. It is concluded that there are determining factors that directly influence the innovative performance of human talent within organizations, especially quality management, direct innovation management, knowledge acquisition and transfer, and technological assets, which are positioned as fundamental pillars to boost innovative capacity at the organizational level.